Absence of association between early antibiotic exposure and short-term adverse outcomes in very preterm infants: a single-center retrospective study - Fillistorf, Laura; Carra, Giorgia; Matusiak, Raphaël; Dimopoulou, Varvara; Despraz, Jérémie; Meylan, Sylvain; Giannoni, Eric (Frontiers in Pediatrics, 2025)
BackgroundAntibiotics save lives but also carry significant risks, including increased antimicrobial resistance, higher healthcare costs, and disruption of the microbiome. However, the association between antibiotic exposure and short-term adverse outcomes remains uncertain. Our study aimed to evaluate whether early unnecessary antibiotic exposure in the first 7 days of life of very preterm infants is linked to short-term adverse outcomes.MethodsThis retrospective study included infants born below 32 weeks of gestation and hospitalized at the University Hospital of Lausanne between January 1, 2007 and December 31, 2022. Antibiotic exposure was quantified during the first seven postnatal days by the median number of days of antibiotics. Multilinear regressions and mixed effect models analyzed the association between the number of days of antibiotics and death, late-onset sepsis, necrotizing enterocolitis, severe bronchopulmonary dysplasia, severe retinopathy of prematurity and cystic periventricular leukomalacia. The primary outcome was a composite of at least one of the listed adverse outcomes, while the secondary outcomes consisted of each adverse outcome individually. Adjusted odds ratio (aOR) and p-value were calculated.ResultsWe included 1,398 preterm infants. The median gestational age was 29 weeks (IQR: 27–30) and the median birthweight was 1,144 grams (895–1,420). The median number of days of antibiotics declined by 53%, from 4 days in 2007 to 1.9 days in 2022 (p < 0.0001). The number of days of antibiotics was not associated with the composite outcome [aOR: 0.97 (0.82–1.17), p = 0.80, adjusted p = 0.80] or any of the following adverse outcomes: mortality [aOR: 1.10 (0.78–1.55), p = 0.58, adjusted p = 0.69], late-onset sepsis [aOR: 0.74 (0.59–0.93), p = 0.01, adjusted p = 0.07], necrotizing enterocolitis [aOR: 1.22 (0.86–1.74), p = 0.26, adjusted p = 0.65], severe bronchopulmonary dysplasia [aOR: 1.12 (0.88–1.42), p = 0.36, adjusted p = 0.65], severe retinopathy of prematurity [aOR: 1.34 (0.65–2.78), p = 0.43, adjusted p = 0.65], and cystic periventricular leukomalacia [aOR: 1.02 (0.69–1.99), p = 0.91, adjusted p = 0.91].ConclusionWe found no association between early antibiotic exposure and short-term adverse outcomes.